Design of a butler matrix beamforming circuit at 28 GHz for 5G mobile communication - Zhang, Bei Bei, 1990-, author 614624; Noor Asniza Murad, supervisor 486393; Fakulti Kejuruteraan Elektrik 540663 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Kejuruteraan (Elektronik dan Telekomunikasi))